1991
DOI: 10.1111/j.1471-0528.1991.tb13451.x
|View full text |Cite
|
Sign up to set email alerts
|

The variation of endometrial response to a standard hormone replacement therapy in women with premature ovarian failure. An ultrasonographic and histological study

Abstract: Summary. The endometrial response to a standard hormone replacement therapy in 18 women with premature ovarian failure was examined by serial ultrasonographic measurement of endometrial thickness and histological study of endometrial biopsy taken on day 19 of the cycle. Women with idiopathic ovarian failure (n = 10) had significantly better response than women with Turner's syndrome (n = 4), whereas women with premature ovarian failure associated with previous chemotherapy (n = 4) had an intermediate response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…This could be due to inadequate uterine development during artificial pubertal induction or due to inherent characteristics of the endometrial and uterine receptors in women with Turner syndrome. Li et al [27] studied the endometrial response to a standard hormone replacement therapy in 18 women with POF aged 26-32 years (10 women with idiopathic POF, 4 women with Turner syndrome and 4 women with POF following chemotherapy). He concluded that following standard HT the endometrium of women with Turner syndrome was significantly less matured both in thickness and histology compared with endometrium in women with other causes of POF.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This could be due to inadequate uterine development during artificial pubertal induction or due to inherent characteristics of the endometrial and uterine receptors in women with Turner syndrome. Li et al [27] studied the endometrial response to a standard hormone replacement therapy in 18 women with POF aged 26-32 years (10 women with idiopathic POF, 4 women with Turner syndrome and 4 women with POF following chemotherapy). He concluded that following standard HT the endometrium of women with Turner syndrome was significantly less matured both in thickness and histology compared with endometrium in women with other causes of POF.…”
Section: Introductionmentioning
confidence: 99%
“…In women with POF, the lack of steroidogenic activity necessitates exogenous steroids to prepare and maintain the endometrium for implantation. For successful implantation of the embryo in women with POF, adequate endometrial preparation by either vaginal or intramuscular progesterone following sufficient estrogen priming is required [27,[41][42][43][44][45][46][47]. The decrease in the serum progesterone levels or the duration of the progesterone exposure leads to luteal phase deficiency [44,45] and inadequate endometrial receptivity, resulting in reduced implantation and pregnancy rates [46].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, we did not observe any influence of HRT on HbA 1c values after adjusting for age and BMI, and we only observed the HbA 1c -lowering effect of HRT in women aged 40 -49 years. Although the cellular mechanisms regulating the age-dependent response of HbA 1c to estrogen have yet to be elucidated, this is also the case for endometrium (28) and bone (29).…”
Section: Research Design Andmentioning
confidence: 99%
“…The endometrial response to a standard HT in 18 women with premature ovarian failure was examined by Li et al (20). Histologic study of endometrial biopsy taken on day 19 of the cycle revealed secretory changes in all patients and positively correlated with endometrial thickness.…”
Section: Discussionmentioning
confidence: 99%